2011
DOI: 10.1039/c0sc00386g
|View full text |Cite
|
Sign up to set email alerts
|

Pattern generation with synthetic sensing systems in lipid bilayer membranes

Abstract: The objective of this study was to introduce differential sensing techniques to synthetic systems that act, like olfactory receptors, as transporters in lipid bilayer membranes. Routine with most alternative chemosensing ensembles, pattern generation has, quite ironically, remained inaccessible in lipid bilayers because the number of available crossresponsive sensor components has been insufficient. To address this challenge, we here report on the use of cationic hydrazides that can react in situ with hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
145
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(150 citation statements)
references
References 39 publications
(98 reference statements)
2
145
1
2
Order By: Relevance
“…[27] Without modification, these analytes are essentially undetectable with most synthetic sensing systems that operate in lipid bilayer membranes. However, their incubation with cations G1H1-G1H3 and A1H1-A1H3 that contain at least one hydrazide gives hydrazones, such as G1H1O1-G1H3O13, and A1H1O1-A1H3O13, which in turn can activate polyanions, such as calf thymus DNA (ctDNA) as cation transporter in fluorogenic vesicles (Figures 1 and Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[27] Without modification, these analytes are essentially undetectable with most synthetic sensing systems that operate in lipid bilayer membranes. However, their incubation with cations G1H1-G1H3 and A1H1-A1H3 that contain at least one hydrazide gives hydrazones, such as G1H1O1-G1H3O13, and A1H1O1-A1H3O13, which in turn can activate polyanions, such as calf thymus DNA (ctDNA) as cation transporter in fluorogenic vesicles (Figures 1 and Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[27] Incubation of analytes with different reactive counterions produces a small collection of in-/activators of synthetic transport systems (Figure 1). From the fluorescent response to increasing activator concentrations, characteristics, such as the maximum normalized response as determined after 190 s (Y MAX ), the effective concentration to reach 50 % of this maximal activity (EC 50 ), or the Hill coefficient (n) are extracted to generate analyte specific patterns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…different kind of molecules. An interesting study on the use of lipid vesicles for sensing odorants has been reported (Takeuchi et al, 2011). Although the core mechanism was based on chemical transformation, it is possible to think to similarly working biomolecular networks.…”
Section: Potential Applications Of Minimal Semi-synthetic Cells and Omentioning
confidence: 99%